Evaluation of anamnestic criteria for the identification of patients with acute community onset viral gastroenteritis in the emergency department—A prospective observational study. (August 2014) - Andreasson, Thomas; Gustavsson, Lars; Lindh, Magnus; Bergbrant, Ing-Marie; Raner, Christina; Åhrén, Christina; Westin, Johan; Andersson, Lars-Magnus
Abstract Background: To our knowledge no clinical criteria for the identification of community onset viral gastroenteritis in individual patients have been evaluated systematically with modern PCR-based diagnostic assays as gold standard. Objective: The aim of this study was to identify factors independently associated with the detection of virus by PCR in rectal swab samples from patients with acute community onset gastroenteritis. Methods: A prospective observational study was conducted from December 2010 through March 2011 at the emergency department (ED) of a large teaching hospital. All patients who reported vomiting and/or diarrhoea up to 48 h prior to their visit to the ED were asked to participate. A rectal swab sample was obtained from each patient. Symptoms, date of onset, and epidemiological data were recorded. Samples were analysed with a multiple real-time PCR targeting 6 viral agents (astrovirus, adenovirus, rotavirus, sapovirus, and norovirus GI and GII). Results: Two hundred and five patients fulfilled the inclusion criteria, of whom 66 agreed to participate; their median (IQR) age was 65 (38–84) y and 43 (65%) were females. Thirty-one (47%) were positive by PCR for at least 1 of the agents examined (26 norovirus, 2 sapovirus, 2 rotavirus, and 1 adenovirus). Diarrhoea and a short duration of symptoms (≤ 2 days) were independently associated with a positive rectal swab sample, with odds ratios of 7.5 (95% confidence interval (CI) 2.0–28) and 10.4 (95% CI 1.9–56), respectively (p < 0.01 for both). A multivariate model including these 2 variables had a sensitivity of 81% (25/31) and a specificity of 69% (24/35). Conclusions: Diarrhoea and a short duration of symptoms were the only anamnestic criteria independently associated with acute community onset viral gastroenteritis confirmed by PCR.